Guardians of Bukit Marang: A political sociology of Dayak Kanayatn indigenous forest management - Resalina, Resalina; Bariyah, Khairul; Nevia, Ahasela Marta; Guteres, Riko; Safitri, Margaretha Dwi; Zhan, Fuzy Firda (Privietlab, 2026)
Customary forest management is an integral part of environmental sustainability and welfare of Indigenous communities. This article aims to review the role of the Dayak Kanayatn indigenous community in the management of the Bukit Marang Customary Forest from a political sociology perspective. This study focuses on the interactions between traditional values, public policies, and socio-political dynamics that influence forest resource management. This study used a descriptive research design with a qualitative approach. Primary and secondary data were obtained from the literature. The results show that the Dayak Kanayatn community plays an essential role in forest conservation, guided by a solid customary system and local wisdom principles. These roles from the socio-political review of this study include (1) forest conservation guardians, (2) local knowledge-based forest management, (3) customary law enforcers, (4) cultural and spiritual custodians, (5) biodiversity protectors, (6) land conflict mediators, and (7) promoters of sustainable development. This article recommends steps to strengthen the empowerment of Indigenous communities in facing current socio-political dynamics through collaboration between actors ranging from the government, advocacy organizations, and communities.